Studying the Location of the Control of the Students of the High Schools in Zakho District and its Relation to the Social and Scientific Variables - Mohammad, Nasraddin I. (Humanities Journal of University of Zakho, 2018)
The search aims to identify locus of control among high school’s students in the center of Zakho, to identify differences between them depending on the variables (Gender, specialty, class, state of parents' life, parent's level of cultural, and family's economic level and rank of student's birth). The sample of research consisted of (376) students selected randomly from Zakho high schools.For this purpose researcher prepared a scale, consisting of (26) items, where extracted psychometric properties, and for the purpose of processing data was used appropriated statistical methods. And the results shows that most of the students have internal locus of control, also found there is statically significant differences according to variables of( sex, class, and level of parents academic situation ) and also found there is no statically significant differences according to variables of (specialty, state of parents' life, and family's economic level), and in the light of the results researchers presented some recommendations and proposals.